2005
DOI: 10.1371/journal.pbio.0030293
|View full text |Cite
|
Sign up to set email alerts
|

Linking New Information to a Reactivated Memory Requires Consolidation and Not Reconsolidation Mechanisms

Abstract: A new memory is initially labile and becomes stabilized through a process of consolidation, which depends on gene expression. Stable memories, however, can again become labile if reactivated by recall and require another phase of protein synthesis in order to be maintained. This process is known as reconsolidation. The functional significance of the labile phase of reconsolidation is unknown; one hypothesis proposes that it is required to link new information with reactivated memories. Reconsolidation is disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 41 publications
(54 reference statements)
8
87
1
1
Order By: Relevance
“…However, by using the same dose of AN in the same task, we can have an indication of the duration of this crucial stage for long-term memory formation. With respect to this stage, the durations of consolidation and reconsolidation evolve in parallel during development; in the adult, similarities and differences between them are still being explored (Dudai 2004;Alberini 2005;Tronel et al 2005;Davis and Laroche 2006;Sara and Hars 2006;Tronson and Taylor 2007). The parallelism observed here during postnatal development suggests that both involve some common processes.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, by using the same dose of AN in the same task, we can have an indication of the duration of this crucial stage for long-term memory formation. With respect to this stage, the durations of consolidation and reconsolidation evolve in parallel during development; in the adult, similarities and differences between them are still being explored (Dudai 2004;Alberini 2005;Tronel et al 2005;Davis and Laroche 2006;Sara and Hars 2006;Tronson and Taylor 2007). The parallelism observed here during postnatal development suggests that both involve some common processes.…”
Section: Discussionmentioning
confidence: 79%
“…Considering the very short period during which the AN was effective at the end of nursing, we tested the effect of AN at a dose of 210 mg/kg, the highest dose generally used in the adult (Davis et al 1980;Tronel et al 2005), in post-weaning rats at the age of P35. The animals were autonomous, so they were submitted to a conventional paradigm of conditioned taste aversion where they were allowed to drink aromatized water (CS) from pipettes and 30 min later poisoned (US) by LiCl injection.…”
Section: Effect Of a High Dose Of An On Post-weaning Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, data support hippocampal involvement in both consolidation and reconsolidation (Debiec et al, 2002;Rossato et al, 2006), and, in contrast, data support that hippocampus is involved in consolidation but not in reconsolidation (Taubenfeld et al, 2001;Tronel et al, 2005).…”
Section: Introductionmentioning
confidence: 77%
“…Thus, one main function of reconsolidation is considered to be memory updating (Pedreira et al 2004;Rossato et al 2006). Even though Tronel et al (2005) concluded that reconsolidation was not required to link new information to a retrieved memory, Lee (2008) demonstrated that an adaptive function of the reconsolidation process enables the update of memory's content. Without the presence of new information, thus when updating is not necessary, a very well-learned memory does not undergo reconsolidation (Rodriguez-Ortiz et al 2005;Winters et al 2009).…”
mentioning
confidence: 99%